PERFORMANCE AND COMPENSATION MANAGEMENT WITH SPECIAL REFERENCE TO INFORMATION TECHNOLOGY INDUSTRY - Basariya, S. Rabiyathul; Jafar Mohammad, Rahim (International Journal of Psychosocial Rehabilitation, 2019)
Compensation management is one of the most important aspects of personnel management. It covers economic rewards in form of wages and salaries as well as in various forms of non-wage economic payment known as fringe benefits, indirect compensation or supplementary pay. Therefore, this research work has been carried out to look at the impact of organizational compensation management system on the performance of employees in the public sector. The result will focus focuses on the analysis of data collected from the field using the questionnaire. It includes the frequency distribution table and the chi-square analysis as well as the inferences made from the analysis. The need for this study arises from the variation in performance of employees in the organization that has been noticed and this research work hoped to improve the standard and in order to achieve this, project has gone into so many past works of authors and related literatures in order to profound solutions